Financing development the role of information costs - Greenwood, Jeremy 1953-; Sanchez, Juan M. 1978-; Wang, Cheng 1965- (Working paper series / National Bureau of Economic Research, 2007)
How does technological progress in financial intermediation affect the economy? To address this question a costly-state verification framework is embedded into a standard growth model. In particular, financial intermediaries can invest resources to monitor the returns earned by firms. The inability to monitor perfectly leads to firms earning rents. Undeserving firms are financed, while deserving ones are under funded. A more efficient monitoring technology squeezes the rents earned by firms. With technological advance in the financial sector, the economy moves continuously from a credit-rationing equilibrium to a perfectly efficient competitive equilibrium. A numerical example suggests that finance is important for growth.